Administrative regulations for the protection of ancient medinas under the law 98_04 on cultural heritage protection - Belmerabet, Hanane (Journal of Human Sciences, 2023)
The old medinas are an authentic urban treasure and a prominent tourist development pole. Numerous factors, such as carelessness or negligence, have aided in the decline of these cities. In this regard, the Algerian legislator has intervened by passing laws and creating specialized organizations to preserve the old medinas as urban cultural properties. This article attempts to elucidate administrative regulations for the protection the approved by the Algerian legislator to protect the ancient medinas in several legal texts, including Law 98/04. This law addresses cultural heritage preservation. In addition, it evaluates the effectiveness of different legal mechanisms in determining the appropriate protection of ancient medinas.